Thermoplastic resin composition
By combining polyphenylene ether-based resin, polyolefin resin and titanium dioxide to form a continuous phase structure, the problem of the polyphenylene ether-based resin being prone to yellowing is solved, high thermal stability and mechanical strength are achieved, and light stability is significantly improved, and it is suitable for a variety of electronic and electrical and industrial products.
Patent Information
- Application Number
- JP2020184656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-04
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2040-11-04
AI Technical Summary
The existing polyphenylene ether-based resin compositions are prone to yellowing under ultraviolet rays, resulting in limited use of color varieties and decreased mechanical strength and thermal stability, making it difficult to widely use in high-demand applications.
By combining polyphenylene ether-based resin, polyolefin resin and titanium dioxide in a specific proportion, a continuous phase structure is formed, and masterbatches are prepared through a twin-screw extrusion mechanism to ensure uniform dispersion of the titanium dioxide, forming a surface cortex, and improving light stability.
The polyphenylene ether-based resin composition has been achieved while maintaining high thermal stability and mechanical strength, and has significantly improved light stability and is suitable for a variety of electronic and electrical and industrial products.
Smart Images

Figure 0007628805000001 
Figure 0007628805000002 
Figure 0007628805000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition. [Background technology]
[0002] Polyphenylene ether (hereinafter, also referred to as "PPE")-based resin-based polyphenylene ether resin compositions (hereinafter, also referred to as "m-PPE resin compositions") have features such as heat resistance, electrical properties, dimensional stability, impact resistance, and low specific gravity. In addition, m-PPE resin compositions can be flame-retarded without using halogen compounds or antimony compounds, which have a large environmental impact, and are therefore widely used in a variety of electrical and electronic parts, office equipment parts, automobile parts, building materials, and other exterior materials and industrial products. In recent years, due to their low dielectric tangent, they are also expected to be used as substrate materials and peripheral components for high-speed communication. However, polyphenylene ether resin compositions tend to turn yellow when exposed to ultraviolet light. Therefore, when coloring the molded product with a chromatic color, especially a bright color such as white, There is a problem in that the applications are limited.
[0003] Patent Document 1 proposes a resin composition made of polyolefin and polyphenylene ether resin that is less susceptible to discoloration due to light by adding a certain amount or more of an inorganic powder selected from the group consisting of titanium oxide having a specific average particle size, mica coated with titanium oxide, barium sulfate, zinc oxide, and zinc sulfide to a polyolefin resin and a polyphenylene ether resin.
[0004] Patent Document 2 reports a method for improving weather discoloration resistance by reducing the content of specific molecular terminal structural units of polyphenylene ether to a predetermined value or less. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication 2004-204013 [Patent Document 2] Patent Publication 2010-189517 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the resin composition disclosed in Patent Document 1, the polyolefin resin forms a continuous phase, and the mechanical strength, heat resistance, and impact resistance are inferior to those of the inherent polyphenylene ether resin, which is a problem.
[0007] Furthermore, in the resin composition disclosed in Patent Document 2, the proportion of polyphenylene ether resin is limited to 50% or less in order to keep the content of terminal hydroxyl groups in polyphenylene ether below a predetermined value, which means that the heat resistance cannot be improved and the extrusion process needs to be carried out in two stages, making it difficult to put into practical use.
[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a thermoplastic resin composition which has excellent resistance to discoloration due to light and which maintains the heat resistance and mechanical strength inherent to polyphenylene ether. [Means for solving the problem]
[0009] As a result of intensive research aimed at solving the above problems, the present inventors have found that by combining a polyphenylene ether resin, a polyolefin resin, and titanium oxide and blending them in a specific ratio, it is possible to provide a thermoplastic resin composition which has excellent resistance to discoloration due to light and which maintains the heat resistance and mechanical strength of polyphenylene ether, thereby completing the present invention.
[0010] That is, the present invention is as follows. [1] A method for producing a thermoplastic resin composition, comprising: The thermoplastic resin composition comprises Contains (A) polyphenylene ether resin, (B) polyolefin resin, and (C) titanium oxide death , Component (A) forms a continuous layer, The content of the (A) component in 100% by mass of the thermoplastic resin composition is 30 to 90% by mass, The mass ratio ((A) / (B)) of the component (A) / the component (B) is 99 / 1 to 70 / 30; The mass ratio of component (B) to component (C) ((B) / (C)) is 50 / 50 to 5 / 95. the law of nature, a masterbatch preparation step of melt-kneading a part or all of the (B) component and a part or all of the (C) component to prepare a masterbatch; a kneading step of melt-kneading the masterbatch obtained in the masterbatch preparation step with the remaining components; Includes A thermoplastic resin composition comprising: Manufacturing method . [2] The method for producing a thermoplastic resin composition according to [1], wherein in the kneading step, the masterbatch and the remaining components are melt-kneaded using an extruder, and the masterbatch is supplied from a supply port located downstream of the extruder. [ 3 ] The thermoplastic resin composition (D) Styrenic resin Fat It also contains, [1] Or [2] The thermoplastic resin composition according to claim 1 Manufacturing method . [4] The method for producing a thermoplastic resin composition according to any one of [1] to [3], wherein the thermoplastic resin composition further contains (E) an elastomer. [ 5 ] The above In the thermoplastic resin composition The mass ratio of component (A) to component (B) ((A) / (B)) is 99 / 1 to 80 / 20. [1] ~[4] The thermoplastic resin composition according to claim 1 Manufacturing method . [ 6 ] The above In the thermoplastic resin composition The mass ratio of component (B) to component (C) ((B) / (C)) is 45 / 55 to 10 / 90, [1] to [ 5
[0023] The thermoplastic resin composition according to any one of the preceding claims. Manufacturing method . [ 7 ] The thermoplastic resin composition (F) [1] to [ 6
[0023] The thermoplastic resin composition according to any one of the preceding claims. Manufacturing method . [8] The method for producing a thermoplastic resin composition according to any one of [1] to [7], wherein a mass ratio ((B) / (C)) of the component (B) / component (C) in the masterbatch is 50 / 50 to 5 / 95. Effect of the Invention
[0011] According to the present invention, it is possible to provide a polyphenylene ether resin composition that has high resistance to discoloration due to light while maintaining heat resistance and mechanical strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail.
[0013] The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of the gist thereof.
[0014] [Thermoplastic resin composition] The thermoplastic resin composition of the present embodiment contains (A) a polyphenylene ether-based resin, (B) a polyolefin resin, and (C) titanium oxide, and further optionally contains (D) a styrene-based resin and / or (E) an elastomer, and (F) a phosphorus-based flame retardant. Here, the component (A) forms a continuous layer in the thermoplastic resin composition. The content of the component (A) in 100% by mass of the thermoplastic resin composition is 30 to 90% by mass. In addition, the mass ratio of component (A) / component (B) ((A) / (B)) is 99 / 1 to 70 / 30, and the mass ratio of component (B) / component (C) ((B) / (C)) is 50 / 50 to 5 / 95.
[0015] In addition, in this specification, (A) polyphenylene ether resin may be referred to as "component (A)," (B) polyolefin resin may be referred to as "component (B)," (C) titanium oxide may be referred to as "component (C)," (D) styrene resin may be referred to as "component (D)," (E) elastomer may be referred to as "component (E)," and (F) flame retardant may be referred to as "component (F)."
[0016] Each component constituting the thermoplastic resin composition will be described in detail below.
[0017] <(A) Polyphenylene ether resin> The thermoplastic resin composition of the present embodiment contains (A) a polyphenylene ether resin. (A) The polyphenylene ether resin is not particularly limited, but is preferably a homopolymer or copolymer having a repeating unit represented by the following general formula (1) and / or general formula (2). As described later, (A) the polyphenylene ether resin may be a modified product having a predetermined modifying group. The (A) polyphenylene ether resin may be used alone or in combination of two or more kinds.
[0018] [ka] [ka] (In general formulas (1) and (2), R 5 , R 6 , R 7 , R 8 , R 9 , R 10 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an aryl group having 6 to 9 carbon atoms, or a halogen atom. 9 , R 10 is not a hydrogen atom at the same time.)
[0019] Examples of the polyphenylene ether homopolymer include, but are not limited to, poly(2,6-dimethyl-1,4-phenylene) ether, poly(2-methyl-6-ethyl-1,4-phenylene) ether, poly(2,6-diethyl-1,4-phenylene) ether, poly(2-ethyl-6-n-propyl-1,4-phenylene) ether, poly(2,6-di-n-propyl-1,4-phenylene) ether, poly(2-methyl-6-n-butyl-1,4-phenylene) ether, poly(2-ethyl-6-isopropyl-1,4-phenylene) ether, poly(2-methyl-6-chloroethyl-1,4-phenylene) ether, poly(2-methyl-6-hydroxyethyl-1,4-phenylene) ether, and poly(2-methyl-6-chloroethyl-1,4-phenylene) ether. Among these, poly(2,6-dimethyl-1,4-phenylene) ether is preferred from the viewpoint of thermal stability.
[0020] The polyphenylene ether copolymer is a copolymer having the repeating units represented by general formula (1) and / or general formula (2) as main repeating units. The term "mainly" means that the polyphenylene ether copolymer contains 60 mass % or more of the repeating units represented by general formula (1) and / or general formula (2).
[0021] The copolymer is not particularly limited, but examples thereof include a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, a copolymer of 2,6-dimethylphenol and o-cresol, and a copolymer of 2,6-dimethylphenol, 2,3,6-trimethylphenol and o-cresol.
[0022] The (A) polyphenylene ether resin may contain polyphenylene ethers containing various phenylene ether units other than those of the general formulae (1) and (2) as partial structures, so long as the heat resistance of the thermoplastic resin composition is not excessively reduced. Examples of such phenylene ether units include, but are not limited to, units derived from 2-(dialkylaminomethyl)-6-methylphenylene ether and units derived from 2-(N-alkyl-N-phenylaminomethyl)-6-methylphenylene ether, as described in JP-A-01-297428 and JP-A-63-301222.
[0023] The reduced viscosity (ηsp / c, chloroform solution, measured at 30° C.) of (A) polyphenylene ether resin is preferably 0.25 to 0.60 dL / g, and more preferably 0.35 to 0.55 dL / g, from the viewpoints of fluidity, toughness, and chemical resistance. The reduced viscosity was measured by preparing a solution of 0.5 g of sample in 100 mL of chloroform and measuring the value at 30° C. using an Ubbelohde viscometer. The unit is dL / g.
[0024] The (A) polyphenylene ether-based resin preferably contains a structure (terminal hydroxyl group-containing portion) represented by the following general formula (3), and the amount of the structure represented by the following general formula (3) (hydroxyl group amount) in the (A) polyphenylene ether-based resin is preferably 0.8 or more, and more preferably 1.0 or more, per 100 repeating units constituting the (A) polyphenylene ether-based resin. [ka] (Wherein, two R 11 , two R 12 each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an aryl group having 6 to 9 carbon atoms, or a halogen atom.
[0025] The amount of hydroxyl groups can be measured using a U3310 spectrophotometer manufactured by Hitachi High-Technologies Corporation, based on the method described in Journal of Applied Polymer Science: Applied Polymer Symposium 34, 103-117 (1978). The amount of hydroxyl groups is expressed as the number of hydroxyl groups represented by the following general formula (3) per 100 repeating units constituting the polyphenylene ether resin (e.g., repeating units derived from 2,6-dimethylphenol constituting poly(2,6-dimethyl-1,4-phenylene) ether).
[0026] The amount of hydroxyl groups in (A) polyphenylene ether resin varies depending on, for example, the conditions for polymerizing a phenolic compound and the conditions for the quinone reaction after the polymerization is terminated. An example of polymerization is described in JP-A-2000-281776 and JP-A-2000-281778 for poly(2,6-dimethyl-1,4-phenylene) ether, and the amount of quinone compound produced varies depending on the amount and time of the additional addition of PPE resin monomer (for example, 2,6-dimethylphenol in the case of poly(2,6-dimethyl-1,4-phenylene) ether) during polymerization. In general, the more the amount of additional addition and the shorter the additional addition time, the greater the amount of quinone compound produced. In the quinone reaction after the polymerization is terminated, the terminal hydroxyl group concentration varies depending on the temperature and time, and the higher the temperature and the longer the time, the higher the hydroxyl group concentration. In the present invention, the conditions for polymerizing the phenolic compound and the conditions for the quinone reaction after termination of the polymerization are not limited, and in general, a quinone compound can be added to the PPE resin obtained by polymerization to cause a quinone reaction to increase the amount of hydroxyl groups.
[0027] In this embodiment, the polyphenylene ether resin (A) can be synthesized by any method. For example, when a catalyst having copper atoms is used, the copper content due to the remaining catalyst is preferably 2.0 mass ppm or less based on the mass of the polyphenylene ether resin. If the copper content of the polyphenylene ether resin exceeds 2.0 mass ppm, the thermal stability of the thermoplastic resin composition decreases, and impact strength may decrease when exposed to high temperatures for a long time. The copper content of the polyphenylene ether resin is preferably 1.0 mass ppm or less, more preferably 0.5 mass ppm or less.
[0028] In this embodiment, the polyphenylene ether resin (A) can be a modified polyphenylene ether obtained by modifying a part or the whole of a polyphenylene ether with an unsaturated or saturated carboxylic acid or a derivative thereof, or a phosphorus-based compound.
[0029] Examples of modified polyphenylene ethers include those described in JP-A-2-276823 (U.S. Pat. No. 5,159,027, U.S. Reissue Patent No. 35,695), JP-A-63-108059 (U.S. Pat. Nos. 5,214,109, 5,216,089), JP-A-59724, and Japanese Patent No. 6,674,477.
[0030] The modified polyphenylene ether can be produced, for example, by melt-kneading and reacting polyphenylene ether with an unsaturated or saturated carboxylic acid or a derivative thereof, phosphonic acids, phosphonic acid esters, phosphinic acids, phosphinic acid esters, monocarboxylic acids, sulfonic acids, sulfinic acids, carbonates, etc. in the presence or absence of a radical initiator. Alternatively, the modified polyphenylene ether can be produced by dissolving polyphenylene ether and an unsaturated or saturated carboxylic acid or a derivative thereof in an organic solvent in the presence or absence of a radical initiator and reacting them in the solution.
[0031] Examples of the unsaturated carboxylic acid or a derivative thereof include, but are not limited to, maleic acid, fumaric acid, itaconic acid, halogenated maleic acid, cis-4-cyclohexene-1,2-dicarboxylic acid, endo-cis-bicyclo(2,2,1)-5-heptene-2,3-dicarboxylic acid, anhydrides of these dicarboxylic acids, esters of these dicarboxylic acids, amides of these dicarboxylic acids, and imides of these dicarboxylic acids; acrylic acid, methacrylic acid, esters of these monocarboxylic acids, and amides of these monocarboxylic acids.
[0032] In this embodiment, examples of the saturated carboxylic acid or a derivative thereof include compounds that can be thermally decomposed at the reaction temperature during the production of the modified polyphenylene ether to become a derivative of the modified polyphenylene ether, specifically, malic acid, citric acid, and the like.
[0033] Examples of phosphonic acids include phosphonic acid (phosphorous acid), methylphosphonic acid, ethylphosphonic acid, vinylphosphonic acid, decylphosphonic acid, phenylphosphonic acid, benzylphosphonic acid, aminomethylphosphonic acid, methylene diphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, 4-methoxyphenylphosphonic acid, and propylphosphonic anhydride.
[0034] Examples of phosphonate esters include dimethyl phosphonate, diethyl phosphonate, bis(2-ethylhexyl) phosphonate, dioctyl phosphonate, dilauryl phosphonate, dioleyl phosphonate, diphenyl phosphonate, dibenzyl phosphonate, dimethyl methylphosphonate, diphenyl methylphosphonate, dioctyl methylphosphonate, diethyl ethylphosphonate, dioctyl ethylphosphonate, diethyl benzylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, dipropyl phenylphosphonate, dioctyl phenylphosphonate, diethyl (methoxymethyl)phosphonate, dioctyl (methoxymethyl)phosphonate, diethyl vinylphosphonate, diethyl vinylphosphonate, diethyl hydroxymethylphosphonate, and hydroxymethylphosphonate. diethyl dimethylphosphonate, (2-hydroxyethyl) dimethyl phosphonate, dioctyl (methoxymethyl) phosphonate, diethyl p-methylbenzyl phosphonate, dioctyl p-methylbenzyl phosphonate, diethyl phosphonoacetic acid, ethyl diethyl phosphonoacetate, tert-butyl diethyl phosphonoacetate, dioctyl diethyl phosphonate, diethyl (4-chlorobenzyl) phosphonate, dioctyl (4-chlorobenzyl) phosphonate, diethyl cyano phosphonate, diethyl cyanomethyl phosphonate, dioctyl cyano phosphonate, diethyl 3,5-di-tert-butyl-4-hydroxybenzyl phosphonate, dioctyl 3,5-di-tert-butyl-4-hydroxybenzyl phosphonate, diethyl (methylthiomethyl) phosphonate, and the like.
[0035] Examples of phosphinic acids include dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylphosphinic acid, diphenylphosphinic acid, dioleylphosphinic acid, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and derivatives thereof.
[0036] Examples of phosphinic acid esters include methyl dimethylphosphinate, ethyl dimethylphosphinate, n-butyl dimethylphosphinate, cyclohexyl dimethylphosphinate, vinyl dimethylphosphinate, phenyl dimethylphosphinate, methyl ethylmethylphosphinate, ethyl ethylmethylphosphinate, n-butyl ethylmethylphosphinate, cyclohexyl ethylmethylphosphinate, vinyl ethylmethylphosphinate, phenyl ethylmethylphosphinate, methyl diethylphosphinate, ethyl diethylphosphinate, n-butyl diethylphosphinate, cyclohexyl diethylphosphinate, vinyl diethylphosphinate, phenyl diethylphosphinate, Examples of such phosphinate include methyl, ethyl diphenylphosphinate, n-butyl diphenylphosphinate, cyclohexyl diphenylphosphinate, vinyl diphenylphosphinate, phenyl diphenylphosphinate, methyl methyl-n-propylphosphinate, ethyl methyl-n-propylphosphinate, n-butyl methyl-n-propylphosphinate, cyclohexyl methyl-n-propylphosphinate, vinyl methyl-n-propylphosphinate, phenyl methyl-n-propylphosphinate, methyl dioleylphosphinate, ethyl dioleylphosphinate, n-butyl dioleylphosphinate, cyclohexyl dioleylphosphinate, vinyl dioleylphosphinate, and phenyl dioleylphosphinate.
[0037] Examples of monocarboxylic acids include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, hexanoic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, tetradecanoic acid, octadecanoic acid, docosanoic acid, hexacosanoic acid, octadecenoic acid, docosenoic acid, and isooctadecanoic acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid and methylbenzenecarboxylic acid; hydroxyaliphatic monocarboxylic acids such as hydroxypropionic acid, hydroxyoctadecanoic acid, and hydroxyoctadecenoic acid; and sulfur-containing aliphatic monocarboxylic acids such as alkylthiopropionic acid.
[0038] Examples of sulfonic acids include alkylsulfonic acid, benzenesulfonic acid, naphthalenesulfonic acid, anthraquinonesulfonic acid, camphorsulfonic acid, and derivatives thereof. These sulfonic acids may be monosulfonic acid, disulfonic acid, or trisulfonic acid. Examples of derivatives of benzenesulfonic acid include phenolsulfonic acid, styrenesulfonic acid, toluenesulfonic acid, and dodecylbenzenesulfonic acid. Examples of derivatives of naphthalenesulfonic acid include 1-naphthalenesulfonic acid, 2-naphthalenesulfonic acid, 1,3-naphthalenedisulfonic acid, 1,3,6-naphthalenetrisulfonic acid, and 6-ethyl-1-naphthalenesulfonic acid. Examples of derivatives of anthraquinonesulfonic acid include anthraquinone-1-sulfonic acid, anthraquinone-2-sulfonic acid, anthraquinone-2,6-disulfonic acid, and 2-methylanthraquinone-6-sulfonic acid.
[0039] Examples of sulfinic acids include alkane sulfinic acids such as ethanesulfinic acid, propanesulfinic acid, hexanesulfinic acid, octanesulfinic acid, decanesulfinic acid, and dodecanesulfinic acid, alicyclic sulfinic acids such as cyclohexanesulfinic acid and cyclooctanesulfinic acid, and aromatic sulfinic acids such as benzenesulfinic acid, o-toluenesulfinic acid, p-toluenesulfinic acid, ethylbenzenesulfinic acid, decylbenzenesulfinic acid, dodecylbenzenesulfinic acid, chlorobenzenesulfinic acid, and naphthalenesulfinic acid.
[0040] Examples of carbonates include dimethyl carbonate, diethyl carbonate, diisopropyl carbonate, dibutyl carbonate, dihexyl carbonate, dioctyl carbonate, diphenyl carbonate, methyl ethyl carbonate, methyl phenyl carbonate, ethyl phenyl carbonate, butyl phenyl carbonate, and ditolyl carbonate.
[0041] These may be used alone or in combination of two or more.
[0042] The polyphenylene ether resin is generally available as a powder. The particle size of the polyphenylene ether resin is preferably 1 to 1000 μm, more preferably 10 to 700 μm, and further preferably 100 to 500 μm, in terms of average particle diameter. From the viewpoint of ease of handling during processing, the average particle size of the polyphenylene ether resin powder is preferably 1 μm or more, and from the viewpoint of suppressing the generation of unmelted material during melt-kneading, it is preferably 1000 μm or less. The average particle size of the polyphenylene ether resin powder can be measured, for example, by a laser granulometer.
[0043] In the thermoplastic resin composition of the present embodiment, the content of component (A) in 100% by mass of the thermoplastic resin composition is 30 to 90% by mass, preferably 40 to 80% by mass, and more preferably 45 to 75% by mass. When the content of component (A) is 90% by mass or less, a good balance between molding flowability and weather discoloration resistance is achieved, and when it is 30% by mass or more, mechanical strength, flame retardancy, and electrical properties are excellent.
[0044] <(B) Polyolefin resin> The thermoplastic resin composition of the present embodiment contains a polyolefin resin (B). The inclusion of the polyolefin resin (B) and titanium oxide (C) described below improves resistance to discoloration due to light. Although the detailed mechanism is not clear, it is believed that the resistance to discoloration due to light can be improved by forming a polyolefin skin layer in which titanium oxide is dispersed on the outermost surface of the thermoplastic resin composition.
[0045] Examples of the polyolefin resin (B) used in the present embodiment include low-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-octene copolymer, and ethylene-acrylic acid ester copolymer. Among them, low-density polyethylene, polypropylene, and high-density polyethylene are preferred. When an elastomer is contained in the composition, the lower the crystallinity of the polyolefin, the better the compatibility with the elastomer and the better the impact resistance. Not only does it become easier to form a polyolefin / elastomer bicontinuous phase on the surface of the molded article, but it is also possible to achieve a balance between weather discoloration resistance and impact resistance with a smaller amount of polyolefin.
[0046] The melt flow rate (MFR) of component (B), measured in accordance with ASTM D-1238 at a cylinder temperature of 230° C., is preferably 0.1 to 50 g / 10 min, and more preferably 2.0 to 25 g / 10 min.
[0047] The mass ratio of the component (A) to the component (B) ((A) / (B)) is from 99 / 1 to 70 / 30, more preferably from 99 / 1 to 80 / 20, and further preferably. By setting the content ratio of component (B) to component (A) at (A) / (B) = 99 / 1 or more, a polyolefin layer is easily formed on the surface of the molded article, improving resistance to discoloration from light. By setting the ratio of component (A) / (B) at or below 70 / 30, polyphenylene ether (A) becomes a continuous phase, improving mechanical strength and heat resistance.
[0048] In the thermoplastic resin composition of this embodiment, the content of component (B) in 100% by mass of the thermoplastic resin composition is preferably 0.3 to 25% by mass, more preferably 1.5 to 15% by mass, and even more preferably 2.5 to 10% by mass.
[0049] <(C) Titanium oxide> The thermoplastic resin composition used in the present embodiment contains titanium oxide (C). By containing the component (C), it is possible to obtain a resin composition having excellent resistance to discoloration due to light.
[0050] From the viewpoint of the balance between dispersibility and surface activity, the primary particle size of the component (C) is preferably 0.01 to 1.0 μm, more preferably 0.05 to 0.8 μm, and even more preferably 0.1 to 0.5 μm.
[0051] The component (C) may contain at least one of hydrous oxides and / or oxides of aluminum, magnesium, zirconia titanium, tin, etc., higher fatty acid salts such as stearic acid, and organosilicon compounds as a surface treatment agent.
[0052] The component (C) can be produced by a dry method or a wet method. The crystal structure of the titanium oxide (C) may be either rutile type or anatase type, but the rutile type is preferred from the viewpoint of the thermal stability of the thermoplastic resin composition used in the present embodiment.
[0053] It is preferable to use a masterbatch of component (C) that has already been compounded with polyolefin resin (B) as a raw material. By using a masterbatch raw material, component (C) is dispersed in a large amount in polyolefin resin (B), and the titanium oxide concentration near the surface of the molded article can be increased.
[0054] The mass ratio (B) / (C) of titanium oxide (C) to polyolefin resin (B) is 50 / 50 to 5 / 95, preferably 45 / 55 to 10 / 90, more preferably 40 / 60 to 12 / 88, and further preferably 35 / 65 to 15 / 85. By making the content ratio of the (C) component to the (B) component, (B) / (C) = 50 / 50 or more, light discoloration resistance is improved, and by making the ratio (B) / (C) = 5 / 95 or less, an excellent balance between light discoloration resistance and mechanical strength is achieved.
[0055] In the thermoplastic resin composition of this embodiment, the content of component (C) in 100% by mass of the thermoplastic resin composition is preferably 0.7 to 45% by mass, more preferably 3.5 to 35% by mass, and even more preferably 6.0 to 28% by mass.
[0056] <(D) Styrene-based resin> The resin composition of this embodiment can contain a (D) styrene-based resin for the purpose of adjusting heat resistance and molding flowability. In this specification, the (D) styrene-based resin does not include those included in the scope of the (E) elastomer described below. The (D) styrene-based resin is not particularly limited, and known resins can be used, including homopolymers of styrene-based compounds; polymers obtained by polymerizing a styrene-based compound and a compound copolymerizable with a styrene-based compound in the presence or absence of a rubber polymer; and the like.
[0057] The styrene-based compound is not particularly limited, and examples thereof include styrene, α-methylstyrene, 2,4-dimethylstyrene, monochlorostyrene, p-methylstyrene, p-tert-butylstyrene, ethylstyrene, etc. Among them, styrene is preferred from the viewpoint of practicality of the raw material. Examples of the compound copolymerizable with the styrene-based compound include methacrylic acid esters such as methyl methacrylate and ethyl methacrylate; unsaturated nitrile compounds such as acrylonitrile and methacrylonitrile; and acid anhydrides such as maleic anhydride.
[0058] As the (D) styrene-based resin, polystyrene is preferred from the viewpoint of miscibility with polyphenylene ether. Among them, rubber-reinforced polystyrene is preferred from the viewpoint of improving impact resistance, and general-purpose polystyrene is preferred from the viewpoint of improving the appearance of molded products. Examples of rubber-reinforced polystyrene include polymers obtained by polymerizing a styrene-based compound and a compound copolymerizable with the styrene-based compound in the presence of a rubber polymer. In the above rubber-reinforced polystyrene, the amount of the compound copolymerizable with the styrene-based compound used is preferably 20% by mass or less, and more preferably 15% by mass or less, relative to 100% by mass of the total amount of the styrene-based compound and the compound copolymerizable with the styrene-based compound. Examples of the rubbery polymer include, but are not limited to, conjugated diene rubber, copolymers of conjugated dienes and aromatic vinyl compounds, ethylene-propylene copolymer rubber, polybutadiene, styrene-butadiene random copolymers, and styrene-butadiene block copolymers, as well as rubber components obtained by partially or almost completely hydrogenating these. The rubber-reinforced polystyrene may be high-impact polystyrene (HIPS), and preferably uses a styrene-butadiene block copolymer as the rubber polymer. The rubber particles of the rubber polymer that constitutes HIPS can be classified into two types: salami structure (multi-cell structure) and polystyrene core (single-cell structure). The above-mentioned "salami structure" refers to a structure in which rubber particles (having a salami sausage cross section) are dispersed in a polystyrene matrix, and multiple polystyrene particles are embedded in a honeycomb shape within the rubber particle phase having a thin outer layer. The above-mentioned "polystyrene core" refers to a core-shell structure in which rubber particles having a single cell structure are dispersed in a polystyrene matrix. The rubber-reinforced polystyrene can be produced by bulk polymerization or bulk suspension polymerization, and the morphology of the rubber particles can be controlled by controlling the stirring conditions in the polymerization process and the mixing conditions during the production of the rubber particles.
[0059] The content of the (D) styrene-based resin in the resin composition of this embodiment is preferably 0 to 70 mass%, more preferably 5 to 50 mass%, and even more preferably 10 to 40 mass%, based on the resin composition (100 mass%). The (D) styrene-based resin is preferably blended from the viewpoint of improving the molding flowability of the resin composition. In addition, from the viewpoint of maintaining sufficient heat resistance, the content of the (D) styrene-based resin is preferably 70 mass% or less.
[0060] <(E) Elastomer> The resin composition of the present embodiment may further contain an elastomer (E) for the purpose of improving impact resistance.
[0061] As the component (E), any known material can be used. From the viewpoints of miscibility with the (A) polyphenylene ether and heat resistance, however, an elastomer containing a block copolymer having a styrene block and a hydrogenated conjugated diene compound block (hereinafter also referred to as a "styrene block-hydrogenated conjugated diene compound block copolymer") is preferred.
[0062] From the viewpoint of thermal stability, the above-mentioned conjugated diene compound block is preferably hydrogenated at a hydrogenation rate of 50% or more, more preferably at a hydrogenation rate of 80% or more, and even more preferably at a hydrogenation rate of 95% or more.
[0063] Examples of the conjugated diene compound block include, but are not limited to, polybutadiene, polyisoprene, poly(ethylene-butylene), poly(ethylene-propylene), vinyl-polyisoprene, etc. The conjugated diene compound block may be used alone or in combination of two or more.
[0064] The arrangement of the repeating units constituting the block copolymer may be either linear or radial. The block structure composed of the polystyrene block and the rubber intermediate block may be any of type 2, type 3, and type 4. Among them, from the viewpoint of being able to fully exert the desired effects of the present embodiment, a type 3 linear block copolymer composed of a polystyrene-poly(ethylene-butylene)-polystyrene structure is preferred. The conjugated diene compound block may contain butadiene units in an amount not exceeding 30% by mass.
[0065] The styrene block-hydrogenated conjugated diene compound block copolymer that can be used in the present embodiment preferably has a weight average molecular weight Mw in the range of 45,000 to 300,000 from the viewpoint of improving impact resistance, more preferably 55,000 to 280,000, and even more preferably 70,000 to 250,000. From the viewpoint of imparting sufficient impact resistance, the weight average molecular weight is preferably 50,000 or more, and from the viewpoints of flowability, appearance retention, and miscibility of the molded article, it is preferably 300,000 or less.
[0066] The bound styrene content of the styrene block-hydrogenated conjugated diene compound block copolymer usable in the present embodiment is preferably in the range of 20 to 80 mass%, more preferably 30 to 60 mass%, and even more preferably 30 to 45 mass%. From the viewpoint of miscibility, the bound styrene content of the styrene block-hydrogenated conjugated diene compound block copolymer is preferably 20 mass% or more, and from the viewpoint of imparting impact resistance, it is preferably 80 mass% or less.
[0067] The content of the (E) elastomer usable in the resin composition of this embodiment is preferably within a range of 1 to 25 mass%, more preferably 3 to 20 mass%, and even more preferably 5 to 15 mass%, based on 100 mass% of the resin composition. The content of the (E) elastomer is preferably 1 mass% or more from the viewpoint of obtaining even better impact resistance, and is preferably 25 mass% or less from the viewpoints of heat resistance and rigidity retention.
[0068] <(F) Flame retardant> The resin constituting the power supply / reception component of this embodiment preferably contains (F) a flame retardant in addition to the above-mentioned components. The (F) flame retardant is not particularly limited, and may be a halogen-based flame retardant, an inorganic flame retardant, a silicone compound, an organic phosphorus compound, or the like, but is preferably at least one selected from the group consisting of inorganic flame retardants, silicone compounds, organic phosphorus compounds, or the like.
[0069] Examples of inorganic flame retardants include alkali metal hydroxides or alkaline earth metal hydroxides such as magnesium hydroxide and aluminum hydroxide, which contain water of crystallization and are generally used as flame retardants for synthetic resins, zinc borate compounds, and zinc stannate compounds.
[0070] The silicone compound may be an organopolysiloxane or a modified product containing an organopolysiloxane, and may be liquid or solid at room temperature. The skeleton structure of the organopolysiloxane may be either a linear structure or a branched structure, but it is preferable that the skeleton structure contains a branched structure or a three-dimensional structure due to the presence of a trifunctional or tetrafunctional structure in the molecule. The bonding group of the main chain or the branched side chain may be hydrogen or a hydrocarbon group, and preferably a phenyl group, a methyl group, an ethyl group, or a propyl group, but other hydrocarbon groups may also be used. The terminal bonding group may be any of -OH, an alkoxy group, and a hydrocarbon group.
[0071] Silicone compounds generally used as flame retardants contain four types of siloxane units (M unit: RSiO 0.5 , D unit: R2SiO 1.0 , T unit: RSiO 1.5 , Q unit: SiO 2.0 In the present embodiment, the preferred organopolysiloxane is a polymer formed by polymerizing any one of the four types of siloxane units represented by the formula RSiO 1.5The organopolysiloxane has 60 mol % or more, more preferably 90 mol % or more, and particularly preferably 100 mol % of siloxane units (T units) represented by the formula: In the total silicone compound used, at least 60 mol %, more preferably 80 mol % or more of the bonded hydrocarbon groups in the total siloxane units represented by the formula R have a phenyl group. Modified silicones in which the bonded groups are substituted with amino groups, epoxy groups, mercapto groups, or other modified groups are also used as these organopolysiloxanes. Modified products in which organopolysiloxanes are chemically or physically adsorbed to inorganic fillers such as silica and calcium carbonate can also be used.
[0072] Examples of the organic phosphorus compound include a phosphoric acid ester compound, a phosphazene compound, etc. The phosphoric acid ester compound is added to improve flame retardancy, and any organic phosphoric acid ester that is generally used as a flame retardant can be used. Specific examples of phosphate ester compounds include triphenyl phosphate, trisnonylphenyl phosphate, resorcinol bis(diphenyl phosphate), resorcinol bis[di(2,6-dimethylphenyl)phosphate], 2,2-bis{4-[bis(phenoxy)phosphoryloxy]phenyl}propane, 2,2-bis{4-[bis(methylphenoxy)phosphoryloxy]phenyl}propane, and the like, but are not limited to these.
[0073] Further, examples of phosphorus-based flame retardants other than those mentioned above include phosphoric acid ester flame retardants such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, trioctyl phosphate, tributoxyethyl phosphate, tricresyl phosphate, cresyl phenyl phosphate, octyl diphenyl phosphate, and diisopropyl phenyl phosphate; diphenyl-4-hydroxy-2,3,5,6-tetrabromobenzyl phosphonate, dimethyl-4-hydroxy-3,5-dibromobenzyl phosphonate, and diphenyl-4-hydroxy-3,5-dibromobenzyl phosphate; monophosphate ester compounds such as phenyl diphenyl phosphate, tris(chloroethyl) phosphate, tris(dichloropropyl) phosphate, tris(chloropropyl) phosphate, bis(2,3-dibromopropyl)-2,3-dichloropropyl phosphate, tris(2,3-dibromopropyl) phosphate, and bis(chloropropyl)monoctyl phosphate, hydroquinonyl diphenyl phosphate, phenyl nonyl phenyl hydroquinonyl phosphate, and phenyl dinonyl phenyl phosphate, as well as aromatic condensed phosphate compounds.
[0074] Among these, aromatic condensed phosphate ester compounds are preferably used because they generate less gas during processing and have excellent thermal stability. These aromatic condensed phosphate ester compounds are generally commercially available, and known examples include CR741, CR733S, and PX200 from Daihachi Chemical Industry Co., Ltd., and FP600, FP700, and FP800 from ADEKA Corporation.
[0075] Particularly preferred is a condensed phosphate ester represented by the following general formula (4) or (5): It is. [ka] [ka] In the general formula (4) and the general formula (5), Q1, Q2, Q3, and Q4 are each a substituent and each independently represent an alkyl group having 1 to 6 carbon atoms; R 13 and R 14 Each represents a methyl group, and R 15 and R 16 each independently represents a hydrogen atom or a methyl group; n is an integer of 1 or more, n1 and n2 each independently represent an integer of 0 to 2, and m1, m2, m3, and m4 each independently represent an integer of 0 to 3.
[0076] The condensed phosphate esters represented by the above general formula (4) and general formula (5) are In the numerator, n is an integer of 1 or more, preferably an integer of 1 to 3.
[0077] Among these, preferred condensed phosphate esters are those in which m1, m2, m3, m4, n1 and n2 in general formula (4) are zero, and R9 and R 10 and a condensed phosphate ester in which Q1, Q2, Q3, Q4, R9 and R 10 is a methyl group, n1 and n2 are zero, and m1, m2, m3 and m4 are integers of 1 to 3, and n is in the range of 1 to 3, and particularly contains 50 mass % or more of a phosphate ester in which n is 1. The one is preferred.
[0078] In the present embodiment, the content of the (F) flame retardant varies depending on the required level of flame retardancy, but is preferably in the range of 5 to 25 parts by mass, more preferably in the range of 5 to 20 parts by mass, and even more preferably in the range of 10 to 25 parts by mass, relative to 100 parts by mass of the (A) polyphenylene ether resin. When the (F) flame retardant content is 5 parts by mass or more, the flame retardancy is excellent, and when it is 25 parts by mass or less, the flame retardancy is sufficient and heat resistance can be maintained.
[0079] [Other ingredients] The resin composition of the present embodiment may further contain other components in addition to the components (A) to (F), such as an antioxidant, an ultraviolet absorber, a hydrolysis inhibitor, an antistatic agent, a lubricant, a release agent, a reinforcing agent, and an acid, within the range that does not significantly deteriorate the heat resistance and mechanical properties of the resin composition, and the surface appearance and light discoloration resistance of a molded product.
[0080] The content of each of the other components in the thermoplastic resin composition of the present embodiment is preferably within a range of 0.001 to 4.0% by mass, more preferably 0.01 to 2.0% by mass, and even more preferably 0.1 to 1.0% by mass, based on the resin composition (100% by mass). From the viewpoint of sufficient addition effect, it is preferably 0.001% by mass or more, and from the viewpoint of sufficient appearance and physical property retention of the molded product, it is preferably 4.0% by mass or less.
[0081] In the resin composition of the present embodiment, an inorganic filler may be blended as a reinforcing agent as another component for the purpose of improving mechanical strength. Inorganic fillers as reinforcing agents are generally used to reinforce thermoplastic resins, and examples of such inorganic fillers include glass fiber, carbon fiber, glass flakes, talc, chlorite, and mica. When an inorganic filler is used as a reinforcing agent as another component, the content of the inorganic filler in the thermoplastic resin composition of the present embodiment is, for example, preferably 50% by mass or less, more preferably 0.5 to 40% by mass, and even more preferably 1 to 30% by mass, relative to the resin composition (100% by mass). The inorganic filler is preferably contained from the viewpoint of improving mechanical strength, and the content of the inorganic filler is preferably 50% by mass or less from the viewpoint of maintaining sufficient appearance of the molded product and molding flowability.
[0082] In the thermoplastic resin composition of this embodiment, the content ratios of the components (A) to (F) are not particularly limited, but from the viewpoint of better achieving the effects of this embodiment, the total content of the components (A) to (F) in 100% by mass of the thermoplastic resin composition is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, and may be 100% by mass.
[0083] Furthermore, when an inorganic filler is used as a reinforcing agent as another component, in the thermoplastic resin composition of this embodiment, when the thermoplastic resin composition excluding the inorganic filler is taken as 100 parts by mass, the total content of the (A) to (F) components can be 90 parts by mass or more, can be 95 parts by mass or more, can be 98 parts by mass or more, or can be 100 parts by mass.
[0084] [Method of producing thermoplastic resin composition] The thermoplastic resin composition of the present embodiment can be produced by melt-kneading the above-mentioned components (A), (B), and (C), and further optionally components (D), (E), and (F), and other components, by appropriately adjusting the melt-kneading conditions.
[0085] In the method for producing the resin composition of the present embodiment, various melt kneaders, kneading extruders, etc. can be used. As the melt kneader or kneading extruder, a known kneader can be used, and examples thereof include extruders such as a single screw extruder, a multi-screw extruder such as a twin screw extruder, etc.; rolls, kneaders, Brabender plastographs, Banbury mixers, etc.; etc. Among them, twin screw extruders are preferred.
[0086] Regarding the conditions for melt-kneading the above-mentioned components (A), (B), (C) and optional components to produce the above-mentioned resin composition, it is preferable to use a twin-screw extruder having a screw diameter of 25 to 90 mm, from the viewpoint of stably obtaining a large amount of a resin composition that can fully exert the desired effects of this embodiment.
[0087] The extrusion temperature is preferably 240 to 360° C., more preferably 260 to 350° C., and further preferably 280 to 330° C. The extrusion temperature is preferably 240° C. or higher from the viewpoint of sufficient compatibility of the constituent components, and is preferably 360° C. or lower from the viewpoints of sufficient retention of mechanical properties, imparting light resistance, and extrudability.
[0088] The supply position of each raw material can be selected from either of the following two methods: (1) supplying component (A) and optional components (D) and (E) from the first supply port in barrel 1 on the upstream side of the flow direction of the twin-screw extruder when melt-kneading, then feeding optional component (F) from the second (liquid) supply port downstream of the first supply port using a gear pump to the side of the extruder through an injection nozzle, and further supplying components (B) and (C) from the third supply port downstream of the second supply port, or (2) supplying components (A), (B), (C), optional components (D) and (E) from the first supply port, and optional component (F) from the second supply port. From the viewpoint that component (B) is likely to form a skin layer on the surface of the molded article, the first method is more preferable.
[0089] It is more preferable that the (B) and (C) components are extrusion-kneaded in advance in a ratio of (B) / (C) of 50 / 50 to 5 / 95. By extrusion-kneading the (B) and (C) components in advance, the (C) component is dispersed more in the (B) component, and when the (B) component forms a skin layer on the surface of the molded article, the (C) component can also be unevenly distributed near the surface at the same time, improving the light discoloration resistance.
[0090] The screw configuration of the twin-screw extruder is such that the unmelted mixing zone is preferably 45 to 75%, and more preferably 60 to 70%, from the upstream side of the barrel when the total barrel length is taken as 100%.
[0091] A suitable molded article in this embodiment has excellent resistance to discoloration due to light, heat resistance, and mechanical strength, and can therefore be used in a variety of applications, such as electronic components, automobiles, home appliances, office equipment, and industrial products. In particular, housings and peripheral components for communication devices are preferred. EXAMPLES
[0092] Hereinafter, the present embodiment will be described more specifically with reference to examples and comparative examples, but the present embodiment is not limited to these examples.
[0093] The methods for measuring physical properties and the raw materials used in the examples and comparative examples are shown below.
[0094] [Method of measuring physical properties] (1) Deflection temperature under load (DTUL) The pellets of the resin composition were dried for 2 hours in a hot air dryer at 90°C. The dried resin composition was molded into a dumbbell-shaped piece of ISO3167, multipurpose test piece type A, using an injection molding machine (Toshiba Machine Co., Ltd., EC75SXII) equipped with an ISO physical property test piece mold, with the cylinder temperature set to 320°C and the mold temperature set to 90°C. The obtained molded piece was cut to prepare a test piece of 80 mm x 10 mm x 4 mm, and the load deflection temperature (°C) was measured at 1.82 MPa by the flatwise method in accordance with ISO75. As an evaluation standard, a temperature of 100°C or higher was determined to be high heat resistance.
[0095] (2) Tensile strength (TS) Using the ISO3167 multipurpose test piece A-type dumbbell molded piece prepared in (1) above, the tensile strength (MPa) was measured at 23°C and a test speed of 5 mm / min in accordance with ISO527, and the average value of 5 measured pieces was calculated. As an evaluation criterion, the higher the average measured tensile strength value, the more excellent the mechanical properties were judged to be, and in particular, a value of 50 MPa or more was judged to be desirable as the resin composition of this embodiment.
[0096] (3) Resistance to discoloration due to light The obtained pellets of the resin composition were dried at 100°C for 2 hours, and then molded into color plates using an EC75SXII injection molding machine (cylinder temperature set at 300°C, mold temperature set at 90°C) manufactured by Toshiba Machine Co., Ltd. The obtained molded pieces were set in a Sunshine Weather Meter (Dew Cycle Sunshine Super Long Life Weather Meter, model: WEL-SUN-DCH type) manufactured by Suga Test Instruments Co., Ltd., and irradiated for 500 hours with a black panel temperature of 65°C and water spray, after which the discoloration of each test plate was measured using a spectrophotometer (Macbeth Color Eye MS-2020+ manufactured by Macbeth Co., Ltd.), and ΔE was calculated according to the following CIE1976 color difference formula. The ΔE of the molded product before the test was ΔE(0), and the ΔE of the UV-exposed surface of the molded product after 500 hours was ΔE(500). ΔE(500)-ΔE(0) was used as an index of discoloration. If ΔE(500)-ΔE(0) was 16 or less, it was determined that the product had excellent weather discoloration resistance. [CIE1976 color difference formula] ΔL * =L * -1 -L * -2 Δa * =a * -1 -a * -2 Δb * =b * -1 -b * -2 ΔE = [(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 ] 1 / 2
[0097] (4) Morphology The center of the parallel part of the ISO3167 multipurpose test piece A-type dumbbell molded piece prepared in (1) above was cut in the MD direction, and the center of the cut surface was adjusted to be smooth using a microtome. After that, for staining, 0.1 g of ruthenium trichloride hydrate, 1 mL of purified water, and 5 mL of sodium hypochlorite were added to a petri dish and reacted, and the sample placed on a wire mesh was placed in the reaction steam and left to stand for 5 minutes. The specimen was then placed under a scanning electron microscope with the stained surface facing up, and the center of the cut surface was observed at 5000x magnification. If the darkest colored phase (PPE) was the sea of the sea-island structure, it was determined that PPE was the continuous phase, and if the lightest colored phase (polyolefin) was the sea of the sea-island structure, it was determined that polyolefin was the continuous phase.
[0098] [raw materials] The components used in each of the examples and comparative examples are as follows.
[0099] [(A) Polyphenylene ether resin (PPE)] Polyphenylene ether obtained by oxidative polymerization of 2,6-dimethylphenol (2,6-xylenol). The reduced viscosity (ηsp / c) is 0.51 dL / g The hydroxyl group concentration is 0.88 per 100 monomer units. Residual copper content 0.6 mass ppm
[0100] [(B) Polyolefin resin (PO)] LDPE: Low-density polyethylene (manufactured by Asahi Kasei Corporation, product name "SUNTEC-LD M2004") PP: Polypropylene (Japan Polypropylene Corporation, product name "NOVATEC-PP MA3")
[0101] [(C) Titanium oxide] TiO2: Rutile titanium oxide, average particle size 0.21 μm (Huntsman, product name "R-TC30")
[0102] [Master batch] MB-1: PP base, TiO2 concentration 70% (manufactured by DIC Corporation, product name "L-11232MPT") MB-2: LDPE base, TiO2 concentration 70% (manufactured by DIC Corporation, product name "L-11186MPT") MB-3: HDPE base, TiO2 concentration 60% (manufactured by DIC Corporation, product name "UF-12766AA") MB-4: PS-based, TiO2 concentration 50% (manufactured by DIC Corporation, product name "PS-F11301")
[0103] [(D) Styrene-based resin] GPPS: General purpose polystyrene (manufactured by PS Japan Co., Ltd., product name "685")
[0104] [(E) Elastomer] SEBS: Polystyrene-poly(ethylene-butylene)-polystyrene copolymer (manufactured by TSPC, product name "TAIPOL6151")
[0105] [(F) Flame retardant] Flame retardant: Bisphenol A condensed phosphate ester (manufactured by Daihachi Chemical Co., Ltd., product name "CR-741")
[0106] [Other ingredients] Mica: Mica (manufactured by Kuraray Co., Ltd., product name "Suzolite Mica 200HK") MAH: Maleic anhydride (manufactured by NOF Corporation, product name "CRYSTAL MAN AB") GF: Glass fiber (manufactured by Nippon Electric Glass Co., Ltd., product name "ECS03T-249")
[0107] [Examples 1 to 6, 9 to 12, Comparative Examples 2, 4, and 6] The components were melt-kneaded using a twin-screw extruder (ZSK-25, manufactured by Coperion, Germany). Specifically, the cylinder temperature was set to 280°C in the front stage and 220°C in the rear stage, and during melt-kneading, components (A), (B), (C), (D), (E) and other components were fed in the amounts shown in Table 1 from a first feed port in barrel 1 on the upstream side in the flow direction of the extruder. Thereafter, a flame retardant as component (F) was fed in the amount shown in Table 1 from the second (liquid) feed port downstream of the first feed port through an injection nozzle on the side of the extruder using a gear pump. Furthermore, components (B), (C), and (D) (all in the form of master batches) and other components were fed from a third feed port downstream of the second feed port to extrude strands. The screw rotation speed was 300 rpm, and the extrusion rate was 15 kg / h. In addition, an opening (vent) was provided in the cylinder block, and the remaining volatile matter was removed by vacuum suction. The degree of vacuum (pressure) at this time was 0.08 MPa. The strand extruded from the die was cooled and cut continuously with a cutter to obtain resin composition pellets of about 3 mm in length and 3 mm in diameter. The resin composition pellets thus obtained were used to carry out the various evaluations described above. The evaluation results are shown in Table 1 below.
[0108] [Examples 7 and 8, Comparative Examples 1, 3, and 5] The components were melt-kneaded using a twin-screw extruder (ZSK-25, manufactured by Coperion, Germany). Specifically, the cylinder temperatures were set to 280°C in the front stage and 220°C in the rear stage, and during melt-kneading, components (A), (B), (C) (including the case where components (B) and (C) are master batches), (D), and (E) were fed in the amounts shown in Table 1 from a first feed port in barrel 1 on the upstream side in the flow direction of the extruder. Thereafter, the flame retardant (E) component was fed from the second (liquid) feed port downstream of the first feed port using a gear pump through an injection nozzle on the side of the extruder to extrude strands. The screw rotation speed was 300 rpm, and the discharge rate was 15 kg / h. In addition, an opening (vent) was provided in the cylinder block, and the remaining volatile matter was removed by vacuum suction. The degree of vacuum (pressure) at this time was 0.08 MPa. The strand extruded from the die was cooled and cut continuously with a cutter to obtain resin composition pellets of about 3 mm in length and 3 mm in diameter. The resin composition pellets thus obtained were used to carry out the various evaluations described above. The evaluation results are shown in Table 1 below.
[0109] [Table 1]
[0110] As shown in Table 1, it was found that, according to Examples 1 to 12, thermoplastic resin compositions excellent in resistance to discoloration due to light and excellent in balance between heat resistance and mechanical strength could be obtained. [Industrial Applicability]
[0111] According to the present invention, it is possible to provide a polyphenylene ether resin composition that has high resistance to discoloration due to light while maintaining heat resistance and mechanical strength.
Claims
1. A method for producing a thermoplastic resin composition, comprising: The thermoplastic resin composition comprises (A) a polyphenylene ether resin, (B) a polyolefin resin, and (C) titanium oxide; Component (A) forms a continuous layer, The content of the component (A) in 100% by mass of the thermoplastic resin composition is 30 to 90% by mass, the mass ratio ((A) / (B)) of the component (A) / the component (B) is 99 / 1 to 70 / 30; the mass ratio ((B) / (C)) of the component (B) / the component (C) is 50 / 50 to 5 / 95; a masterbatch preparation step of melt-kneading a part or all of the (B) component and a part or all of the (C) component to prepare a masterbatch; a kneading step of melt-kneading the masterbatch obtained in the masterbatch preparation step with the remaining components; Includes A method for producing a thermoplastic resin composition, comprising:
2. A method for producing a thermoplastic resin composition as described in claim 1, wherein in the kneading step, the masterbatch and the remaining components are melt-kneaded using an extruder, and the masterbatch is supplied from a supply port located downstream of the extruder.
3. A method for producing a thermoplastic resin composition described in claim 1 or 2, wherein the thermoplastic resin composition further contains (D) a styrene-based resin.
4. A method for producing a thermoplastic resin composition described in any one of claims 1 to 3, wherein the thermoplastic resin composition further contains (E) an elastomer.
5. The method for producing a thermoplastic resin composition according to any one of claims 1 to 4, wherein a mass ratio ((A) / (B)) of the component (A) / component (B) in the thermoplastic resin composition is 99 / 1 to 80 / 20.
6. The method for producing a thermoplastic resin composition according to any one of claims 1 to 5, wherein a mass ratio ((B) / (C)) of the component (B) / component (C) in the thermoplastic resin composition is 45 / 55 to 10 / 90.
7. A method for producing a thermoplastic resin composition described in any one of claims 1 to 6, wherein the thermoplastic resin composition further contains (F) a flame retardant.
8. A method for producing a thermoplastic resin composition described in any one of claims 1 to 7, wherein the mass ratio ((B) / (C)) of the (B) component / (C) component in the masterbatch is 50 / 50 to 5 / 95.
Citation Information
Patent Citations
Composition of polyphenylene ether resin and styrene-bromostyrene copolymer
JP1982021444A
White polyphenylene ether resin composition
JP1983021444A
Impact resistant polyphenylene ether composition
JP1983103556A
Thermoplastic resin composition and molded article
JP2004196974A
Polyphenylene ether-based resin composition, method for producing polyphenylene ether-based resin composition, and molding of polyphenilene ether-based resin composition
JP2010189517A